2016
DOI: 10.1002/cam4.886
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 as a potential therapeutic target for clear cell renal cell carcinoma

Abstract: We previously reported that the pVHL‐atypical PKC‐JunB pathway contributed to promotion of cell invasiveness and angiogenesis in clear cell renal cell carcinoma (ccRCC), and we detected chemokine (C‐C motif) ligand‐2 (CCL2) as one of downstream effectors of JunB. CCL2 plays a critical role in tumorigenesis in other types of cancer, but its role in ccRCC remains unclear. In this study, we investigated the roles and therapeutic potential of CCL2 in ccRCC. Immunohistochemical analysis of CCL2 expression for ccRCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…Although the source of CCL2 in this model is not identified, the same group has shown that a RCC cell line, 786-O, expresses high levels of CCL2. They also demonstrated that suppression of the CCL2 expression in 786-O cells reduces the number of TAMs in the xenograft tumor as well as tumor growth and microvascular density ( 53 ), suggesting that cancer cell-derived CCL2 promotes the TAM accumulation in this model (Figure 2A ). In the 786-O RCC cells, the CCL2 production is increased by JunB overexpression via loss of the von Hippel-Lindau (VHL) tumor suppressor gene ( 54 ).…”
Section: Chemokines That Promote Accumulation Of Pro-metastatic Macromentioning
confidence: 90%
See 3 more Smart Citations
“…Although the source of CCL2 in this model is not identified, the same group has shown that a RCC cell line, 786-O, expresses high levels of CCL2. They also demonstrated that suppression of the CCL2 expression in 786-O cells reduces the number of TAMs in the xenograft tumor as well as tumor growth and microvascular density ( 53 ), suggesting that cancer cell-derived CCL2 promotes the TAM accumulation in this model (Figure 2A ). In the 786-O RCC cells, the CCL2 production is increased by JunB overexpression via loss of the von Hippel-Lindau (VHL) tumor suppressor gene ( 54 ).…”
Section: Chemokines That Promote Accumulation Of Pro-metastatic Macromentioning
confidence: 90%
“…Although the above-mentioned studies suggest CCL2 as a dominant TAM attractant in most solid tumors, CCL2 inhibition suppresses TAM accumulation by only around 50% and does not achieve complete TAM depletion in the mouse models ( 52 , 53 , 56 , 59 61 ). This suggests the involvement of other CCR2 ligands such as CCL12 ( 17 ) and cytokines such as VEGF and CSF1 that are known to recruit monocytes ( 66 , 67 ).…”
Section: Chemokines That Promote Accumulation Of Pro-metastatic Macromentioning
confidence: 97%
See 2 more Smart Citations
“…CCL2 is a chemokine that regulates the migration of monocytes and macrophages. In mice, interference with the CCL2/CCR2 axis significantly reduced the growth of hepatocellular and renal cell carcinomas ( 154 , 155 ), and abrogated breast cancer metastasis ( 119 ). Interestingly, cessation of CCL2 inhibition accelerated breast cancer metastasis by promoting the infiltration of bone-marrow monocytes into tumors ( 156 ), indicating the importance of CCL2 signaling in regulating metastatic growth.…”
Section: Macrophages As a Therapeutic Targetmentioning
confidence: 99%